A Comprehensive Framework for Comparing Textbooks: Insights from the Literature and Experts - Huang, Ronghuai; Tlili, Ahmed; Zhang, Xiangling; Sun, Tianyue; Wang, Junyu; Sharma, Ramesh Chander; Affouneh, Saida; Salha, Soheil Hussein; Altinay, Fahriye; Altinay, Zehra; Olivier, Jako; Jemni, Mohamed; et al. (Sustainable, 2023)
Textbooks are essential components in the learning process. They assist in achieving educational learning outcomes and developing social and cultural values. However, limited studies provide comprehensive frameworks for comparing textbooks. Most have focused on a specific textbook perspective within a particular discipline. Therefore, this study used a triangulation method to develop a comprehensive framework for textbook comparison. Through a systematic literature review and a two-round Fuzzy Delphi method with 155 textbook experts, a textbook comparison framework with four indicators (structure, content, expectations, and language) was developed. Additionally, some of the developed framework indicators and sub-indicators could be relevant for comparing textbooks in a particular discipline. For example, the page count sub-indicator was proven to be useful for comparing humanities and social science textbooks but not natural science textbooks. The findings of this study could facilitate the process of comparing textbooks, hence promoting the understanding of knowledge design and acquisition in different contexts, such as when comparing textbooks from different countries.
Keywords: textbook; comparative; education; framework; systematic review; delphi method; JCR; Scopus